Empowering cassava farmers in Wonogiri through digital financial and marketing strategies - Vitalis Ari Widiyaningsih; Heru Suwasono; Zayid Musiafa (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
Cengklok Village in Wonogiri Regency holds economic potential, particularly in cassava chip production, that remains underutilized. Limited knowledge of financial management and marketing strategies has led to low product value and restricted market access. This community engagement initiative aimed to strengthen farmers' capacities through training in financial record-keeping, cost of production calculation, and digital-based promotion strategies. The activities included field observations, surveys, interviews, problem analysis, training material development, and practical sessions. As a result, participants gained the ability to manage budgets systematically, determine selling prices based on cost analysis, and organize financial records more effectively. Enhancements in visual marketing and product packaging attracted greater consumer interest and broadened market reach. Furthermore, the formation of farmer groups with clear organizational structures contributed to business sustainability. The program improved farmers’ skills in managing agribusinesses professionally, supporting local economic growth and market expansion. The development of cassava chip enterprises as an alternative income source also increased productivity during the off-season, enabling more efficient use of time. This transformation positively impacted farmers’ welfare and ensured the long-term viability of local, commodity-based enterprises.